Linking glucocorticoid action and hypoxia: a novel mechanism driving an adverse metabolic phenotype? - Hazlehurst, J (2018)
Obstructive sleep apnoea (OSA) is characterised by repeated cycles of reduced and complete obstruction of air flow occurring in sleep. This can result in decreased oxygen levels (hypoxia). OSA and states of glucocorticoid excess are both associated with metabolic diseases including fatty liver disease. Whether increased glucocorticoids are a feature of OSA and may contribute to the increased metabolic risk seen in OSA is unknown. In vitro, patient and healthy volunteer studies were employed to assess adipose response to hypoxia. Further metabolic effects of acute and chronic intermittent hypoxia (AIH and CIH) were examined in healthy volunteers and rodents respectively. The AIH study incorporated glucocorticoid receptor (GR) blockade. The patient study also examined the effect of OSA on glucocorticoid availability. Adipocytes were sensitive to extreme hypoxia in vitro although this was not seen in adipose biopsies from patients with OSA or in assessment of adipose function in AIH. AIH in man and CIH in rodents resulted in increased de novo lipogenesis (DNL). Sham CPAP was associated with increased urinary glucocorticoids. GR blockade limited adipose tissue fatty acid mobilisation but did not affect the metabolic impact of AIH on DNL. Intermittent hypoxia drives DNL. OSA is associated with increased glucocorticoids. Despite this GR blockade was not protective against the effects of intermittent hypoxia in this model and is unlikely to be a useful therapeutic target therefore in patients with OSA.